iSCIENCE4ALL - THE OPEN INTERNATIONAL MULTILINGUAL PLATFORM FOR THE SCIENTIFIC & TECHNICAL INFORMATION MANAGEMENT - E. V. Ugrinovich; D. V. Mun (Informaciâ i Innovacii, 2018)
The article based on historical, economic, and socio-psychological analysis substantiates the need for the early formation of an international information platform for storing, exchanging and managing scientific and technical information, based on the principle of “open access” and using a multilingual approach to the formation of scientific data archives.